Forensic discrimination of vermilion stain using thin layer chromatography technique. (2022) - Ghosh, Swagata; Sharma, Tina
Abstract: Cosmetics commodities are often found at the crime scene which gives imperative clues related to the crime and has the ability to establish the link. Vermilion is one such piece of evidence that could be utilized as trace evidence to the link between the suspects, victim, and the scene of the crime. In order to establish the link, the vermilion stain needs to be individualized with respect to inter and intra-specific variations found among the brands available in the market. In the present study, 159 samples of 53 brands were collected. A novel solvent system was developed (Ethanol and Water in the ratio of 90:10 (v/v) which provided high resolution, more spots, and discriminating Rf values as compared to the conventional solvent system available in the literature to discriminate the vermillion stains. The TLC technique with the newly developed solvent system was able to resolve 60% of intra-specific and 90% of inter-specific variations which suggests significant discrimination of vermilion stains